Analisis Pengembangan Sistem Distribusi Pada Sumber Mata Air Desa Lamendora Kecamatan Kapoiala Kabupaten Konawe - Abdillah, Muh. Fiqram; Lakawa, Irwan; Sulaiman, Sulaiman; Ilham, Vickky Anggara (Sultra Civil Engineering Journal (SCiEJ), 2022)
Water is an important component for the life of living things on earth and cannot be separated from the need for water. Water is the main requirement in the process of life on earth so that there is no life if there is no water on earth. Water is an element that is difficult to separate from human life. The importance of the role of water for the life of creatures on the earth's surface, it is necessary to have a water source that can provide water both in terms of quantity and quality. The purpose of this study is to analyze the water demand in Lamendora Village for the next ten years and analyze the water discharge and installation capacity in the process of developing a water distribution system. The water demand for the next 10 years projection for each facility in Lamendora village is for the domestic sector of 0,000607 m/s, for the non-domestic sector the entire facility is 0.0005228 m³/s. The average flow rate of the Lamendora river is 10,988 m³/s, after that the roughness coefficient calculation according to hazzen-wiliams results in 24,189m from brocaptering to the reservoir. As for the flow velocity of 33.21 m3/second. so that the river flow of the Lamendora village can still meet the water needs for the next 10 years.